1999
DOI: 10.1592/phco.19.3.150.30927
|View full text |Cite
|
Sign up to set email alerts
|

Lack of a Pharmacokinetic Interaction at Steady State Between Ropinirole and L‐Dopa in Patients with Parkinson's Disease

Abstract: There are no pharmacokinetic grounds for adjusting dosages of either ropinirole or L-dopa when given in combination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 15 publications
1
8
0
2
Order By: Relevance
“…The accuracy values of processed ropinirole samples (30.0, 4500.0 pg/ml; n = 6) were 1.7% and −5.4%, respectively, when kept at room temperature for 24 h. Table 1 provides its mean pharmacokinetic parameters and range. Ropinirole had approximately linear pharmacokinetics when given as a single dose, and was eliminated with a half-life of approximately 6 h. Peak plasma concentrations of ropinirole were reached within 0.74-2 h. These findings are in agreement with the previously reported pharmacokinetic parameters of ropinirole [6][7][8][9]. Although the mean AUC inf and C max of ropinirole were 16.2% and 8.9% greater respectively in the Madopar phase than in the placebo phase, the other pharmacokinetic parameters were not significantly different between the two phases.…”
Section: Validation Of the Methodssupporting
confidence: 91%
See 1 more Smart Citation
“…The accuracy values of processed ropinirole samples (30.0, 4500.0 pg/ml; n = 6) were 1.7% and −5.4%, respectively, when kept at room temperature for 24 h. Table 1 provides its mean pharmacokinetic parameters and range. Ropinirole had approximately linear pharmacokinetics when given as a single dose, and was eliminated with a half-life of approximately 6 h. Peak plasma concentrations of ropinirole were reached within 0.74-2 h. These findings are in agreement with the previously reported pharmacokinetic parameters of ropinirole [6][7][8][9]. Although the mean AUC inf and C max of ropinirole were 16.2% and 8.9% greater respectively in the Madopar phase than in the placebo phase, the other pharmacokinetic parameters were not significantly different between the two phases.…”
Section: Validation Of the Methodssupporting
confidence: 91%
“…Research about the disposition and metabolic fate of ropinirole has been carried out in animals and humans [5]. Previous work has examined the pharmacokinetics of ropinirole in Caucasian [6][7][8] and has observed the lack of a pharmacokinetic interaction between ropinirole and levodopa plus carbidopa at steady state in Caucasian patients with PD [9]. However the effects of Madopar on the pharmacokinetics of ropinirole in Asians have not yet been examined.…”
Section: Introductionmentioning
confidence: 99%
“…Low (1.5 mg/d) and high (4.5 mg/d) pramipexole doses administered concomitantly with levodopa did not alter levodopa bioavailability in a double‐blind, placebo‐controlled trial 19 . There was no pharmacokinetic interaction reported under coadministration of ropinirole and levodopa in PD patients not previously treated with dopamine agonists 20 …”
Section: Discussionmentioning
confidence: 93%
“…32 A study evaluating the pharmacokinetic interaction of ropinirole and levodopa demonstrated that their co-administration does not affect the bioavailability of ropinirole and may cause an average increase of only 16% in the maximum steady-state concentration of levodopa (see Table 3). 37 However, the study also noted that peak concentrations of levodopa are highly variable and, in some individuals, may increase up to 47% when administered with ropinirole. 37 Yet, in various clinical trials of dopamine agonists, the dose of levodopa was reduced by approximately 20% in patients with a positive clinical response to the adjunctive therapy, demonstrating that pharmacodynamic interactions may be of greater clinical significance (see Table 3).…”
Section: Frontiers In Neuropharmacotherapy Part IImentioning
confidence: 91%
“…37 However, the study also noted that peak concentrations of levodopa are highly variable and, in some individuals, may increase up to 47% when administered with ropinirole. 37 Yet, in various clinical trials of dopamine agonists, the dose of levodopa was reduced by approximately 20% in patients with a positive clinical response to the adjunctive therapy, demonstrating that pharmacodynamic interactions may be of greater clinical significance (see Table 3). 32,[38][39] …”
Section: Frontiers In Neuropharmacotherapy Part IImentioning
confidence: 91%